2018
DOI: 10.1111/jcpp.12978
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal study of parent‐reported sensory responsiveness in toddlers at‐risk for autism

Abstract: Background Atypical sensory responsivity and sensory interests are now included in the DSM 5 diagnostic criteria for autism spectrum disorder (ASD) under the broad domain of restricted and repetitive behavior (RRB). However, relatively little is known about the emergence of sensory‐related features and their relation to conventionally defined RRB in the first years of life. Methods Prospective, longitudinal parent‐report data using the Sensory Experiences Questionnaire (SEQ) were collected for 331 high‐risk to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
65
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 57 publications
(87 citation statements)
references
References 60 publications
(97 reference statements)
9
65
1
Order By: Relevance
“…One of the first clinical features of ASD are atypical responses to or interests in sensory stimuli [ 3 ]. These changes in sensory function likely result from the diminished ability to filter sensory information [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…One of the first clinical features of ASD are atypical responses to or interests in sensory stimuli [ 3 ]. These changes in sensory function likely result from the diminished ability to filter sensory information [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many similar instruments, for example, the Modified Checklist for Autism in Toddlers (M-CHAT; Robins et al, 2014), Ages and Stages Questionnaires (ASQs; Bricker et al, 1999), and Communication and Symbolic Behavior Scales (CSBS; Wetherby & Prizant, 2002), largely focus on typical and atypical language development and social-communicative functioning in early childhood. However, recent findings suggest that many, although not all, infants at risk for developing ASD show atypical early sensory behavior (Turner-Brown et al, 2013; Wolff et al, 2019) and this behavior may serve as an early predictor of later ASD diagnosis (Sacrey et al, 2018). Considering a high prevalence of atypical sensory features in ASD (DuBois et al, 2017) and their recognition as important features of ASD diagnostic criteria in the Diagnostic and Statistical Manual of Mental Disorders (4th ed., text rev.…”
Section: Discussionmentioning
confidence: 99%
“…Germani et al [44] found that EL-ASD showed abnormalities in the auditory processing compared to EL-TD and TL while no difference was found in the visual, tactile, vestibular and oral domains. On the contrary, Wolff et al [53] reported anomalies in all sensory subdomains.…”
Section: Sensory Processing (N = 5; Table 7)mentioning
confidence: 91%
“…Similarly, the use of body and play materials in a self-stimulatory way at 12 months was predictive towards ASD [33]. In Germani et al [44] sensory abnormalities at 24 months in EL-ASD were limited to the auditory domain, while Wolff et al [53] extended them to all sensory domains. These results might suggest that sensory atypicalities might be a specific trait for children who develop ASD not seen at a sub-threshold level.…”
Section: Sensory Domainmentioning
confidence: 95%
See 1 more Smart Citation